2013
DOI: 10.1038/nn.3369
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the accumbal indirect pathway promotes resilience to compulsive cocaine use

Abstract: A hallmark of addiction is the loss of control over drug intake, which is seen only in a fraction of those exposed to stimulant drugs like cocaine. The cellular mechanisms underlying vulnerability or resistance to compulsive drug use are still unknown. Here we show that individual variability in the development of highly motivated and perseverative behavior toward cocaine is associated with synaptic plasticity in medium spiny neurons expressing dopamine D2 receptors (D2-MSNs) in the nucleus accumbens of mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
241
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(264 citation statements)
references
References 35 publications
23
241
0
Order By: Relevance
“…S5, ii). These results demonstrate that cocaine-induced PRMT6 down-regulation in the NAc occurs specifically in D2-MSNs, where it counteracts the rewarding effects of cocaine, thus reinforcing the hypothesis that this MSN subtype is necessary for opposing cocaine use (26).…”
Section: Significancesupporting
confidence: 72%
“…S5, ii). These results demonstrate that cocaine-induced PRMT6 down-regulation in the NAc occurs specifically in D2-MSNs, where it counteracts the rewarding effects of cocaine, thus reinforcing the hypothesis that this MSN subtype is necessary for opposing cocaine use (26).…”
Section: Significancesupporting
confidence: 72%
“…MSNs primarily express D1-like or D2-like dopamine receptors. Though we were not in a position to address the identity of c-Fos-positive neurons in TLR4 -/-mice in the current study, we think these neurons may be D2-MSNs as activation of these neurons mainly controls aversive behaviors [37][38][39]. It is well-known that D2-MSNs are inhibited by DA [40], and xenobiotic activation of TLR4 results in an increase in DA in the NAc [20,33].…”
Section: Discussionmentioning
confidence: 80%
“…Strengthening of excitatory synapses in MSNs in the NAc involves the initial formation of silent synapses lacking AMPA receptors during chronic exposure to cocaine, followed by insertion of AMPA receptors into spines during withdrawal (9)(10)(11). Accumulating evidence indicates that adaptive cocaine action involves potentiation of glutamatergic afferents arising from mPFC, amygdala, and ventral hippocampus preferentially onto D1-MSNs (41-44), although D2-MSNs still contribute to certain behavioral features of cocaine action (45,46). Previous studies showed that WAVE1 is highly localized to dendritic spines (47).…”
Section: Discussionmentioning
confidence: 99%